T.S. Kuhn se bydrae tot die wetenskapsleer - Swanepoel, J. (Koers, 1982)
In this paper the author gives an exposition of T.S. Kuhn’s contribution to the philosophy and historiography of science. He discusses Kuhn’s rejection of the “received view "of science and places Kuhn’s critique on Logical Positivism within the framework of an historicist and sociological approach to the philosophy of science. The author pays attention to Kuhn s rival theory on the revolutionary growth oj science, with special reference to the role of the disciplinary matrix and exemplars in the formation of scientific knowledge. Kuhn’s differences form and attack on the basic premises oj the “received view" are clearly slated. After this exposition the author briefly evaluates Kuhn's influential contribution to the philosophy of science. He concludes with some remarks on the relevance of Kuhn’s theories for a Christian view of science.